Pedagogical Possibilities of using "Soft Skills" in the Professional Development of Teachers - Shahodat Teshaboyeva (International Journal on Integrated Education, 2022)
In the article, the pedagogical possibilities of using "soft skills" in the professional development of teachers are discussed, including the ability to manage oneself in pedagogical activities, control stress situations, monitor personal improvement, know time management, show initiative, be persistent, and approach work with enthusiasm. stated. The manifestation of "soft skills" skills in teachers is based on social-communicative skills, organizational skills, functional skills.